Examining the connections between teacher self efficacy and parental involvement practices - Chliara, Panagiota; Sampedro-Requena, Begoña; Alonso-García, Santiago (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Teacher self-efficacy and parental involvement are closely connected and can both have a significant impact on student success. Objectives. This article examines the connections between teacher self-efficacy and parental involvement practices. The idea that parental involvement and teacher self-efficacy have a positive influence on students’ academic achievement is widely accepted. Methods. A quantitative study was conducted to examine the levels of self-reported self-efficacy and parental involvement of 600 special education teachers in Greece. Results. The results revealed that teacher self efficacy is significantly positively correlated with parental involvement in pedagogical work. Conclusion. Overall, the research reviewed in this article suggests that special education teachers in Greece with a high level of self-efficacy involve parents in the education of their students more often. This is very important because high levels of parental involvement can contribute to better education of students with special needs.